2001
DOI: 10.1523/jneurosci.21-19-07481.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of Two Voltage-Gated Sodium Channel Mutations That Cause Generalized Epilepsy with Febrile Seizures Plus Type 2

Abstract: Two mutations that cause generalized epilepsy with febrile seizures plus (GEFS+) have been identified previously in the SCN1A gene encoding the alpha subunit of the Na(v)1.1 voltage-gated sodium channel (Escayg et al., 2000). Both mutations change conserved residues in putative voltage-sensing S4 segments, T875M in domain II and R1648H in domain IV. Each mutation was cloned into the orthologous rat channel rNa(v)1.1, and the properties of the mutant channels were determined in the absence and presence of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 33 publications
8
142
2
4
Order By: Relevance
“…Separate disease-causing mutations in Na v 1.4 and Na v 1.5, as well as our previously published data for the GEFSϩ mutation R1648H in Na v 1.1, demonstrate that more rapid recovery from inactivation can result in sodium channel-mediated hyperexcitability (Hayward et al, 1996; Q. Chen et al, 1998;Spampanato et al, 2001). We therefore analyzed the effects of the D1866Y mutation on recovery from inactivation in the absence and presence of the ␤1 subunit (Fig.…”
Section: The D1866y Mutation Does Not Alter the Voltage Dependence Ofsupporting
confidence: 72%
See 2 more Smart Citations
“…Separate disease-causing mutations in Na v 1.4 and Na v 1.5, as well as our previously published data for the GEFSϩ mutation R1648H in Na v 1.1, demonstrate that more rapid recovery from inactivation can result in sodium channel-mediated hyperexcitability (Hayward et al, 1996; Q. Chen et al, 1998;Spampanato et al, 2001). We therefore analyzed the effects of the D1866Y mutation on recovery from inactivation in the absence and presence of the ␤1 subunit (Fig.…”
Section: The D1866y Mutation Does Not Alter the Voltage Dependence Ofsupporting
confidence: 72%
“…Second, the ␤1 subunit has a clear and easily quantifiable effect on the properties of ␣ subunit sodium channels in oocytes, so that we could reliably determine whether the ␣ subunit mutation altered modulation by ␤1. Third, the data could be directly compared with our previous results for three other GEFSϩ mutations with respect to both the effects on sodium channel properties and the predicted effects on neuronal firing using a computational model (Spampanato et al, 2001(Spampanato et al, , 2003(Spampanato et al, , 2004. It is important to note that although the oocyte expression system provides a powerful means to determine biophysical differences between mutant and wild-type channels, there have been functional differences as well as similarities between observations in oocytes and in mammalian-transfected cells for some mutants (Spampanato et al, 2001(Spampanato et al, , 2003Lossin et al, 2002).…”
Section: The D1866y Mutation Does Not Alter the Voltage Dependence Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…21 SCN1A mutations responsible for GEFS þ cause only minor changes in channel kinetics. 23,32 Polymorphic sodium channel variants, such as those described here, may contribute to the range of cognitive and emotional function in normal individuals. The combined effect of variants in multiple ion channel genes could also predispose to psychiatric disorders such as autism.…”
Section: Discussionmentioning
confidence: 92%
“…Both mutations changed evolutionarily invariant residues located in the voltage-sensing S4 segments of the protein. Introduction of these mutations into the SCN1A channel and examination of the kinetic properties in Xenopus oocytes demonstrated that the R1648H mutation accelerated the recovery from inactivation and decreased the use dependence of channel activity (66). This accelerated recovery could lead to rapid firing patterns and neuronal hyperexcitability.…”
Section: Generalized Epilepsy With Febrile Seizures Plus-mentioning
confidence: 99%